Knowledge Sharing Among Employees at WXY Automotive Sdn. Bhd. Kuala Lumpur - ismail, fadillah; Nur Azia Hazida Mohamad Azmi,; Nur Amalina Mohd Rosli, (Advances in Humanities and Contemporary Studies, 2025)
In today’s competitive global market, effective knowledge management is crucial for maintaining a competitive edge. Many studies have explored the relationship between factors influencing knowledge sharing and employees’ willingness to share knowledge in foreign countries. However, there is limited research on this topic within Malaysian companies. This study aims to determine the relationship between organizational support, rewards, and perceived loss of authority on employees' willingness to share knowledge at WXY Automotive Sdn Bhd. Using a quantitative approach, data were collected via questionnaires distributed to the company's employees. The results indicate that organizational support and rewards significantly influence employees' willingness to share knowledge. Therefore, WXY Automotive Sdn Bhd should create a supportive environment that encourages knowledge sharing. This can be achieved by organizing regular training sessions, workshops, and forums where employees can share their insights and experiences.To motivate employees to share knowledge, WXY Automotive Sdn Bhd should develop a comprehensive reward system. This should include both monetary and non-monetary incentives, such as bonuses, recognition programs, career advancement opportunities, and public acknowledgment of employees' contributions. Clearly communicating these incentives and applying them consistently will encourage more employees to engage in knowledge-sharing activities.